Extracellular Vesicles, New Players in Sepsis and Acute Respiratory Distress Syndrome - Jing, Wenqiang; Wang, Huijuan; Zhan, Liying; Yan, Wei (Frontiers in Cellular and Infection Microbiology, 2022)
Sepsis refers to a complex syndrome associated with physiological, pathological, and biochemical abnormalities resulted from infection. Sepsis is the major cause of acute respiratory distress syndrome (ARDS). Extracellular vesicles (EVs) are serving as new messengers to mediate cell-cell communication in vivo. Non-coding RNAs, proteins and metabolites encapsulated by EVs could result in either pro-inflammatory or anti-inflammatory effects in the recipient cells. Pathogens or host cells derived EVs play an important role in pathogens infection during the occurrence and development of sepsis and ARDS. Additionally, we summarize the potential application for EVs in diagnosis, prevention and treatment for sepsis and ARDS.